KONSEP MODERASI DAN SOSIAL ISLAM: MELAWAN EKSTRIMISME DALAM AGAMA - Abdul Aziz, Muhammad (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Moderation is a middle-class attitude and view (wasatiyah) that is not excessive, not extreme and not radical (tatharruf). It is stated as in Q.S. al-Baqarah: 143. This paper discusses the principle of moderation (an aspect of al-wasatiyyah) in Islamic social concepts. The author emphasizes the concept of moderation in tradition like a platform to combat extremism in multi-religious and multi-racial societies. The fact that moderation as a concept is found in other religions and traditions, it justifies the idea that moderation enters into universal notions. The author uses descriptive, analytical and textual qualitative methodologies applied to written material related to the subject matter. The findings reveal that religious leaders thoroughly consider concepts in their discourse. Some universal shared values, such as fairness, balance, and patience can be found in both traditions and are useful in deradicalizing existing potentials and extremists.